2014
DOI: 10.1177/1933719113512533
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Maternal Zearalenone Exposure on Uterine Capacity and Fetal Development in Gestation Rats

Abstract: The objectives of this study were to determine the effects of high-dose and early gestational exposure to zearalenone (ZEN) in female Sprague-Dawley (SD) rats, to correlate the maternal uterus with the fetus, and to explore the development and malformation of fetuses. Pregnant female SD rats were fed diets containing 0.3, 48.5, 97.6, or 146.0 mg/kg ZEN on gestational days (GDs) 0 through 7. All the females survived until GD 20, at which point a cesarean section was performed to harvest the organs, blood, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 62 publications
2
38
1
Order By: Relevance
“…Studies in pigs showed an impact on the reproductive capacity of dams fed a naturally contaminated diet (0.2e1 mg ZEN/kg feed). Other studies reported delayed fetal development in rats administered high doses (48.5e146 mg ZEN/kg feed) (Schoevers et al, 2012;Zhang et al, 2014). In contrast to the isoflavones, ZEN binds to both ER isoforms with similar affinity (reviewed in Metzler et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Studies in pigs showed an impact on the reproductive capacity of dams fed a naturally contaminated diet (0.2e1 mg ZEN/kg feed). Other studies reported delayed fetal development in rats administered high doses (48.5e146 mg ZEN/kg feed) (Schoevers et al, 2012;Zhang et al, 2014). In contrast to the isoflavones, ZEN binds to both ER isoforms with similar affinity (reviewed in Metzler et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The detrimental effects of ZEN may be more obvious during pregnancy because the foetus is susceptible to toxins due to its fragile developmental state and lack of adequate defence mechanisms. Studies have indicated that maternal ZEN exposure induces a delay of foetal development in rats and reduced litter size in the sows (Diekman & Long et al 1989;Zhang, Jia, et al 2014). The early events of pregnancy are associated with rapid changes in the *Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…The trans-generational effects of ZEN have been studied in the reproductive system of rats, mice and pigs (Nikaido et al 2004;Schoevers et al 2012;Zhang, Jia, et al 2014). It is hypothesised that maternal ZEN exposure can damage the immune function of pregnant sows and the offspring, and increase the death rate of neonatal and weaning piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Zearalenone frequently occurs in piglets under natural conditions, which are caused by ZEN exposure in the uterus and placental transfer from the exposed sow to her piglets or by the stored ZEN during gestation release via suckling the piglets [8]. Exposure to ZEN during gestation can delay the fetal development and lead to premature oocyte depletion in adulthood of the offspring [9,10]. At the beginning of gestation in pigs, the maternal and fetal blood is separated by the endothelial cells of the maternal blood vessels, maternal connective tissue, and endometrial epithelial cells (epitheliochorial placenta), which affects the direct contact of the maternal blood with the fetal chorion.…”
Section: Introductionmentioning
confidence: 99%